Variation of Platelet Indices Among Patients with Acute Stroke and the Need for their Routine Documentation - Bharatwaj, Anish S; Esaki, Muthuvel; E, Yogalakshmi; Ellappalayam, Architha (Annals of Pathology and Laboratory Medicine, 2018)
Background: Acute Stroke is characterized by sudden appearance of focal deficit of brain function most commonly hemiplegia, which may be accompanied by higher centre dysfunction, sensory loss and visual field defects. Based on the pathology, it is classified as Ischemic or Hemorrhagic stroke. In both the conditions, there is an inevitable involvement of platelets. In the former, platelet activation leading to a thrombus formation is the pathogenic feature whereas in the latter, platelet activation to stop the bleeding is seen. In this study we aim to find the association between Platelet Count, Platelet Indices; Mean Platelet Volume (MPV), Platelet Distribution Width (PDW) and Stroke. Methods: It was a prospective study done in which 70 consecutive patients were divided into ischemic and hemorrhagic strokes. Proper Exclusion criteria were carried out and the patients’ blood samples were taken. Platelet indices were measured with a SYSMEX analyser. Statistical analysis was done using 2 sample T Tests using SPSS software. Result: The Parameters MPC, MPV and PDW all showed a significant association (P=0.04, P=0.00, P=0.00 respectively) between the stroke patients and control group. Furthermore, a significant difference was found between MPC of patients with ischemic and hemorrhagic stroke (P=0.025). Conclusion: Platelet Indices are altered in patients with Stroke when compared to normal patients with no history of CAD or CVD or other lifestyle diseases. Further studies and researches have to be undertaken to see if Platelet Indices are indeed a worthy prognostic tool.